Exploring Movement Impairments in Patients With Parkinson's Disease Using the Microsoft Kinect Sensor: A Feasibility Study - Rudå, Ditte; Einarsson, Gudmundur; Andersen, Anne Sofie Schott; Matthiassen, Jannik Boll; Correll, Christoph U.; Winge, Kristian; Clemmensen, Line K. H.; Paulsen, Rasmus R.; Pagsberg, Anne Katrine; Fink-Jensen, Anders (Frontiers in Neurology, 2021)
BACKGROUND: Current assessments of motor symptoms in Parkinson’s disease, as well as of antipsychotic-induced motor symptoms in psychiatric patients, are often limited to clinical rating scales. OBJECTIVES: To develop a computer application using the Microsoft Kinect sensor to assess performance-related bradykinesia. METHODS: The developed application (Motorgame) was tested in patients with Parkinson’s disease and healthy controls. Participants were assessed with the Movement Disorder Society Unified Parkinson's disease Rating Scale (MDS-UPDRS) and standardized clinical side effect rating scales, i.e., UKU Side Effect Rating Scale and Simpson-Angus Scale. Additionally, tests of information processing (Symbol Coding Task) and motor speed (Token Motor Task), together with a questionnaire, were applied. RESULTS: Thirty patients with Parkinson’s disease and 33 healthy controls were assessed. In the patient group, there was a statistically significant (p<0.05) association between prolonged time of motor performance in the Motorgame and upper body rigidity and bradykinesia (MDS-UPDRS) with the strongest effects in the right hand (p<0.001). In the entire group, prolonged time of motor performance was significantly associated with higher Simson-Angus scale score rigidity score and higher UKU hypokinesia scores (p<0.05). A shortened time of motor performance was significantly associated with higher scores on information processing (p<0.05). Time of motor performance was not significantly associated with Token Motor Task, duration of illness, or hours of daily physical activity. The Motorgame was well accepted. CONCLUSIONS: The Motorgame was able to detect common motor symptoms in Parkinson’s disease in a statistically significant and clinically meaningful way, making it applicable for further testing in larger samples.